Does Chronic Cannabis Use Impact Risky Decision-Making: An Examination of fMRI Activation and Effective Connectivity? - Raymond, David R.; Paneto, Adrian; Yoder, Karmen K.; O'Donnell, Brian F.; Brown, Joshua W.; Hetrick, William P.; Newman, Sharlene D. (Frontiers in Psychiatry, 2020)
With the increase in use of cannabis and its shifting legal status in the United States, cannabis use has become an important research focus.  While studies of other drug populations have shown marked increases in risky decision-making, the literature on cannabis users is not as clear.  The current study examined the performance of 17 cannabis users and 14 non-users on the Balloon Analogue Risk Task (BART) using behavioral, fMRI and effective connectivity methods.  Significant attenuation was found in a functional pathway projecting from the dorsal anterior cingulate cortex (dACC) to the nucleus accumbens (NAc) in cannabis users compared to non-using controls as well as decreases in risk-taking behaviors.  These findings suggest that cannabis users may process and evaluate risks and rewards differently than non-users.